OAUNI photometry of SN 2023ijd - Pereyra, Antonio (2023)
Photometry of Type II SN 2023ijd (TNSTR-2023-1092, TNSCR-2023-1112) was gathered with the OAUNI 51cm telescope (arXiv:1512.03104) at Huancayo Observatory, Peru. CCD imaging in R filter was performed on three consecutive nights under non-photometric conditions with airmasses lower than 1.8. The integration time was 70x20s=1400s in each observation. Our measurements yielded: Date (UT) / filter / seeing (") / mag ; 2023-07-15.072 / R / 2.1 / 15.52 +/- 0.01 ; 2023-07-16.057 / R / 1.8 / 15.61 +/- 0.01 ; 2023-07-17.053 / R / 2.2 / 15.56 +/- 0.01. UCAC4 field stars were used for the zero point calibration. Our observations are ~two months after the ASAS-SN detection (TNSTR-2023-1092). The OAUNI project is supported by UNI, TWAS, IGP and ProCiencia-Concytec (Convenio 133-2020 Fondecyt).